PELATIHAN PEMANFAATAN AI UNTUK MEMBUAT VIDEO KREATIF - Arnomo, Sasa Ani; Kremer, Hendri; Aritonang, Mhd Adi Setiawan; Jabnabillah, Faradiba; Yulia, Yulia (PUAN INDONESIA, 2025)
Lack of support from parents, teachers, or peers can make students feel unmotivated to develop creativity. Therefore, an activity is needed that helps develop students' talents other than academics. AI training in video making has opened up new opportunities for school students to explore creativity. Making videos is not just a hobby, but also has many benefits for student development. It helps students explore new ideas, think out-of-the-box, and find unique ways to express themselves. In addition, it is very important to equip students with digital skills that are in great demand in the modern era, such as operating video editing software, searching for information online, and using various creative applications.